DEI Dilemma at AFT Capital - Carter, Jon; Westerman, James W. (Journal of Knowledge Management Practice, 2025)
Ryan Stevens is staring down a decision that could define his legacy. At the helm of AFT Capital’s inaugural fund, he’s got one shot left—one final investment that could determine not just the fund’s performance, but his future in venture capital. The stakes? Immense. With investors watching closely, and with AFT’s DEI promises etched into its identity, Ryan is caught in a high-stakes tug-of-war. SecureChain looks like a grand slam—technologically robust, market-ready, and led by a proven team. But its leadership lacks diversity, a detail that’s impossible to ignore. The two alternative startups boast minority founders and strong DEI alignment, yet their financial trajectories are riskier. Ryan is wrestling with the hardest question of his career: does he chase the clearest path to returns—or invest in the change he claims to believe in?